(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The electronic, structural, mechanical and superconducting properties of PtH and IrH are investigated using first principles calculation based on density functional theory with generalized gradient approximation. The calculated lattice constants at normal pressure are in good agreement with experimental and other theoretical results. Among the five crystallographic proposed structures investigated, the cubic phase is found to be more stable than the hexagonal ones. A new high pressure CsCl phase is predicted for Iridium hydride. The maximum superconducting transition temperature achieved in Platinum hydride and Iridium hydride are 23.8K and 10K respectively. The calculated elastic constants indicate that both the hydrides are mechanically stable at ambient pressure.